Mythological origins and mapping of plants in Turkish garden art - Tanrısever, Canan (Tourism and Recreation, 2025)
Turkish culture, deeply rooted in nature and influenced by diverse interactions with various civilizations, holds a unique gardening tradition dating back thousands of years. This study explores the evolution of Turkish gardening culture, focusing on Istanbul’s historical peninsula, and examining plant species’ roles in shaping cultural identity and tourism narratives. Beginning with the ancient nomadic and spiritual practices in Central Asia, the study traces the influence of major religious shifts, including Islam, which introduced the "Paradise Garden" concept. The Ottoman period further refined Turkish gardens, integrating influences from Mediterranean, Iranian, and Byzantine sources while maintaining a distinct natural harmony. Ottoman gardens flourished, emphasizing functionality, spirituality, and symbolic plant use, with species like roses, tulips, and cypress trees gaining prominence. This research aims to document and map plant species found in Istanbul’s prominent historical sites, linking each to its mythological roots. Utilizing Geographic Information Systems (GIS), the study creates visual representations of these plants, supporting their narrative use by tour guides, and enhancing tourists' engagement with Istanbul's heritage. The findings underscore the cultural and mythological significance of these plants, offering insights into Turkish garden aesthetics and their symbolic evolution. By highlighting mythological storytelling in tourism, this study also provides practical implications for heritage preservation, tourism enrichment, and urban planning, inviting future research on plant symbolism across cultures and its integration into modern urban spaces.